y = -x + 1/3
+ x + x
--------------------------
x + y = 1/3
Step-by-step explanation:
<u>Given functions:</u>
<u>Find (f*g)(6):</u>
- (f*g)(6) = f(6)*g(6) = 6(6 - 1)*3(6) = 30*18 = 540
<u>In case it is a composite function (f · g)(6) the answer is different:</u>
- (f · g)(6) = f(g(6)) = f(3*6) = f(18) = 18*(18 - 1) = 306
Answer:
8i + 4
Step-by-step explanation:
Add/subtract like terms:
7 - 3
= 4
-4i - (-12i)
-4i + 12i
= 8i
Add these together:
8i + 4
So, the simplified expression is 8i + 4
Answer:
y = -0.5x + 100
Step-by-step explanation:
Im not really sure what i was supposed to answer but i hope it helped.